Women’s Empowerment and Political Participation in Cross River South Senatorial District - EBONG, Offiong Erete; ODOCK, Christopher N. (International Journal of Law and Society, 2022)
This research empirically examined the level of women's empowerment and political participation in the Cross River South Senatorial District (CRSSD), which comprises Akampka, Akpabuyo, Bakassi, Biase, Calabar Municipality, Calabar South, and Odukpani Local Government Areas. A purposive sampling procedure was used to select the study's sample population. 259 structured questionnaires (used as data) were evenly distributed to respondents in the aforementioned local government areas. Using the split-half, test, and retest procedures, these structured questionnaires were validated and evaluated for reliability to assure the credibility and use of the data collected for this study. The data obtained from our survey was subjected to descriptive and inferential statistical analysis to confirm the hypotheses generated to guide the study. The results revealed that women are underrepresented in governance and decision-making positions in the Cross River South Senatorial District. It was also noticed that women should have reacted favourably to the limited possibilities for increased political participation that were presented to them. Traditional gender roles, gender-based stereotypes and discriminatory attitudes, violence against women in politics, and a lack of financial resources were significant factors discouraging women from participating in politics. This work concludes that marginalised women's views must be heard for societal progress and development.